CUMULATIVE PREGNANCY RATE AFTER ELECTIVE SINGLE EMBRYOTRANSFER: THE IMPACT OF EMBRYO VITRIFICATION PROGRAMME - Borut Kovačič; Mirko Vlaisavljević; Milan Reljič; Vida Gavrić-Lovrec; Vilma Kovač; Martin Ivec (Zdravniški Vestnik, 2018)
Background: Multiple pregnancies are undesired consequence of infertility treatment by in vitro fertilization (IVF). In 2008 the Health Insurance Institute of Slovenia strove for lowering the number of multiple pregnancies. It widened the rights of patients by reimbursement of two additional IVF cycles, having totally six cycles reimbursed. But in women younger than 36, only one top-quality embryo in the first two IVF cycles has to be transferred. The aim of the study was to assess, how the new approach, including also the transfers of frozen-thawed embryos, influenced the IVF outcomes. Methods: In year 2008, the transfer of one optimal embryo had to be done in 47.4 % (287/650) of IVF cycles. The criteria for optimality of early cleavage stage embryos were: at least 6 blastomeres and less than 20 % of fragmentation; and for blastocysts: expanded blastocoel and oval inner-cell-mass. Embryos were cultured to blastocysts in 79.4 % (228/287) of cycles. The surplus blastocysts were vitrified in 172 cycles. The transfer of devitrified blastocysts was performed in 82 patients, which did not conceive in fresh cycle. The pregnancy rate and twins rate after fresh transfers and after transfers of devitrified embryos were analyzed. Results: Single embryo or blastocyst transfer was done in 58.9 % of women. In the remaining 41.1 % of cycles the embryos were morphologically not optimal and we decided for double embryo or blastocyst transfer. In the group in which a single and mostly the only embryo was trans- ferred, only 17.2 % of women became pregnant. After the transfer of elective single blastocyst, 51.4 % of women conceived. After double blastocyst transfer, 40.9 % of patients conceived and 50 % of them had twins. The replacement of devitrified blastocysts was successful in 23.2 %. The cumulative pregnancy rate in group of cycles with single fresh blastocyst transfer, followed by transfers of devitrified blastocysts, was 62.9 %. The cumulative pregnancy and multiple pregnancy rate in the whole group was 50.9 % and 14.4 %, respectively. Conclusions: By the policy of reduction the number of transferred embryos into the uterus in IVF pro- gramme, the multiple pregnancy rate decreased from previously 40 % down to 14.4 %.